GEOPOLITICA Y APARATO LIBIDINAL DE LOS DISCURSOS RACCIONARIO Y LIBERAL: PARA UNA GENEAOLOGIA NO MODERNA DE LA OBRA DE MESONERO ROMANOS Y DONOSO CORTES - Gabilondo, Joseba (Res Publica. Revista de Historia de las Ideas Políticas, 2009)
(…)This essay studies comparatively the work of Donoso Cortés and Spanish literary “costumbrismo”, which is a defining discourse for early 19th century Spanish liberalism. It attempts to show the discursive continuity between reactionary thought and liberal culture (…)